PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MENGGUNAKAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI CAHAYA DI SMPN 03 KOTA BENGKULU - Yusuf Bahtiar; Nirwana Nirwana; Dedy Hamdani (UNIB Press, 2017)
Application of problem-based learning model using scientific approach to improve the activity and learning outcomes of students of class VIII.2 on light material at SMPN 03 Bengkulu. The purpose of this study is to determine the increase in student activity and learning outcomes in four cycles in light matter. The subjects of this study are all students of class VIII.2 with the number of 40 people. The instruments used are activity observation sheets, attitude observation sheet, skill observation sheet, and knowledge test sheet. The results of this study indicate that student learning activity in cycle I is categorized well with the average score of 35, increased on the second cycle of 37.5, again increased in the third cycle of 39, and on IV cycle of 41. Student learning outcomes on aspects Attitude increases in each cycle. In cycle I average score obtained 12,625 good category, cycle II 13,01 good category, cycle III 13,15, and cycle IV 14,06 category very good. The learning outcomes in the skills aspect also increase in each cycle and are categorized well. Average score on cycle I is 81,03, at cycle II 82,60, 84,58, and 91,25. The learning outcomes on the average value of knowledge in the first cycle is 76 and the completeness of classical learning is 75% (unfinished), the average value in cycle II is 75.375 and the completeness of classical learning is 80% (unfinished), the average value in cycle III is 77.75 And classical learning completeness 85% (complete), and the average value in the cycle IV of 79.125 and 90% complete (90%) classical learning completeness. Based on the results of the study it can be concluded that the application of problem-based learning model using scientific approach can improve student activity and learning outcomes. Keywords: problem-based learning model, scientific approach, student learning activity